Clinical Impact of Metagenomic Next-Generation Sequencing of Plasma Cell-Free DNA for the Diagnosis of Infectious Diseases: A Multicenter Retrospective Cohort Study. (14th January 2020) - Hogan, Catherine A; Yang, Shangxin; Garner, Omai B; Green, Daniel A; Gomez, Carlos A; Dien Bard, Jennifer; Pinsky, Benjamin A; Banaei, Niaz
Abstract: Background: Metagenomic next-generation sequencing (mNGS) of plasma cell-free DNA has emerged as an attractive diagnostic modality allowing broad-range pathogen detection, noninvasive sampling, and earlier diagnosis. However, little is known about its real-world clinical impact as used in routine practice. Methods: We performed a retrospective cohort study of all patients for whom plasma mNGS (Karius test) was performed for all indications at 5 United States institutions over 1.5 years. Comprehensive records review was performed, and standardized assessment of clinical impact of the mNGS based on the treating team's interpretation of Karius results and patient management was established. Results: A total of 82 Karius tests were evaluated from 39 (47.6%) adults and 43 (52.4%) children and a total of 53 (64.6%) immunocompromised patients. Karius positivity rate was 50 of 82 (61.0%), with 25 (50.0%) showing 2 or more organisms (range, 2–8). The Karius test results led to positive impact in 6 (7.3%), negative impact in 3 (3.7%), and no impact in 71 (86.6%), and was indeterminate in 2 (2.4%). Cases with positive Karius result and clinical impact involved bacteria and/or fungi but not DNA viruses or parasites. In 10 patients who underwent 16 additional repeated tests, only 1 was associated with clinical impact. Conclusions: The real-world impact of the Karius test as currently used in routine clinical practice is limited. Further studies are needed to identify high-yield patient populations, define the complementary role of mNGS to conventional microbiological methods, and discern how best to integrate mNGS into current testing algorithms. Abstract : In a multicenter retrospective cohort study, we show that the real-world clinical impact of plasma metagenomic next-generation sequencing (mNGS) for the noninvasive diagnosis of infections is limited (positive impact, 7.3%). Further studies are needed to optimize the impact of mNGS.